2001
DOI: 10.1128/aem.67.8.3702-3706.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Granulovirus Isolated from Epinotia aporema Wals. (Lepidoptera: Tortricidae) Larvae

Abstract: A granulovirus (GV) isolated from Epinotia aporema (Lepidoptera: Tortricidae)-a major soybean pest-was studied in terms of its main morphological, biochemical, and biological properties. The ovoidal occlusion bodies were 466 by 296 nm in size, and their most prominent protein had an apparent molecular mass of 29 kDa. Its amino-terminal sequence was remarkably homologous to that of the granulins of other GVs. The DNA genome size was estimated to be 120 kbp. The high specificity and pathogenicity of this newly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
(31 reference statements)
6
25
0
6
Order By: Relevance
“…These cells were rounded and developed nuclear hypertrophy. Same data was observed by Sciocco-Cap et al (23), showing in the histological analysis of the 4th instar of Epinotia aporema larva (Lepidoptera, Tortricidae) infected with Baculovirus that were presented the same phases of cellular disruption.…”
Section: Histopathology In Vitrosupporting
confidence: 66%
“…These cells were rounded and developed nuclear hypertrophy. Same data was observed by Sciocco-Cap et al (23), showing in the histological analysis of the 4th instar of Epinotia aporema larva (Lepidoptera, Tortricidae) infected with Baculovirus that were presented the same phases of cellular disruption.…”
Section: Histopathology In Vitrosupporting
confidence: 66%
“…The virus used in this study was propagated in and purified from initially healthy larvae infected by diet surface contamination with the characterized EpapGV isolate as reported previously [6,19]. The virus titer was estimated using a dark-field microscope by counting the number of OBs in a Petroff-Hausser chamber.…”
Section: Insects and Virus Sourcementioning
confidence: 99%
“…Crocidosema) aporema Wals. (Lepidoptera: Tortricidae) [6,12,16,19]. Initial studies on virus-host interactions were performed using optical and electron microscopy [6,19], and an attempt to measure the accumulation of the major viral protein (granulin) after per os ingestion involved the production of polyclonal antibodies [17].…”
Section: Introductionmentioning
confidence: 99%
“…A recently discovered granulovirus of E. aporema (EpapGV) (Sciocco-Cap et al 2001;Goldberg et al 2002) has been shown as a promising biological control agent when ingested by early larval instars. This led to the establishment of a laboratory-reared insect colony supplied with artificial diet, both to perform pathogen-host interaction studies and for virus multiplication.…”
Section: Biologia E Morfometria Dos Estágios Imaturos De Epinotia Apomentioning
confidence: 99%
“…The available information on E. aporema life cycle is limited and mostly restricted to its occurrence and development on soybean crops under variable conditions (Morey, 1972;Iede & Foerster, 1982). Nevertheless, some basic aspects of the insect biology and morphometrics are still poorly documented.Traditionally, various chemical insecticides have been used against this moth, but the interest in more environmentally friendly biopesticides such as Bacillus thuringiensis and baculoviruses has increased in the past few years (Ibarra et al 1992;Sciocco-Cap et al 2001;Sauka et al 2007). A recently discovered granulovirus of E. aporema (EpapGV) (Sciocco-Cap et al 2001;Goldberg et al 2002) has been shown as a promising biological control agent when ingested by early larval instars.…”
mentioning
confidence: 99%